HERMENEUTIK SUFI : Sebuah Kajian atas Pandangan Ibn Arabi tentang Takwil al-Qur'an - Noer, Kautsar Azhari (Sekolah Tinggi Filsafat Islam (STFI) Sadra, 2012)
This article is an attempt to analyze Ibn 'Arabi's view of ta'wÄ«l (esoteric commentary) of the Qur'an. This Sufi Master of Andalusia refuses the ta'wÄ«l controlled by reasoning, reflection, thinking, and desire because such ta'wÄ«l deviates from what God meant by His words contained by His Book. But he accepts the ta'wÄ«l guided by God through intuitive unveiling (kashf), that is, the ta'wÄ«l bestowed by God to those whom He gave success in understanding what God meant by His words contained by His Book. This ta'wÄ«l, which is advocated by Ibn 'Arabi, maintains the coformity between the outward meaning and inward meaning